Musicality in Samuel Taylor Coleridge’s Kubla Khan - Hasan Hussein Karo (QALAAI ZANIST JOURNAL, 2024)
This paper discusses the definition and the use of sound devices in Samuel Taylor Coleridge’s Kubla Khan (1816) which creates the poem’s musicality. It shows the biography of the life of the poet and his contributions to English literature. A short clarification of the poem Kubla Khan will be presented in this paper along with the main literary techniques such as alliteration, assonance, consonance, onomatopoeia and rhyme, responsible for creating the musicality in the poem with reference to the lines in the poem. The paper highly focuses on the language used to answer the questions raised in this research in which it makes the paper discourse analytic research. It is worth noting that the conclusion in the paper provides the existence of musicality in the poem